Evaluation of the Diagnostic Accuracy of PET/MRI in the Staging of Prostate Cancer: A Retrospective Study in Barcelona, Spain - Paula Guelle; Sandra Quinn (Sriwijaya Journal of Radiology and Imaging Research, 2025)
Introduction: Accurate staging of prostate cancer (PCa) is crucial for treatment planning and prognostication. The integration of positron emission tomography (PET) and magnetic resonance imaging (MRI) into a single hybrid system (PET/MRI) has shown promise in improving PCa staging accuracy. This study aimed to evaluate the diagnostic accuracy of PET/MRI in the staging of PCa in a cohort of patients from Barcelona, Spain. Methods: A retrospective analysis was conducted on 120 patients with biopsy-proven PCa who underwent PET/MRI for staging between 2018 and 2023 at a tertiary care center in Barcelona. PET/MRI findings were compared with the histopathological results from radical prostatectomy or biopsy as the reference standard. Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and accuracy were calculated for PET/MRI in detecting local tumor extent (T-stage), lymph node involvement (N-stage), and distant metastases (M-stage). Results: PET/MRI demonstrated a sensitivity of 92%, specificity of 88%, PPV of 90%, NPV of 91%, and accuracy of 90% for T-staging. For N-staging, the sensitivity, specificity, PPV, NPV, and accuracy were 85%, 94%, 82%, 95%, and 92%, respectively. In the detection of distant metastases (M-stage), PET/MRI showed a sensitivity of 90%, specificity of 98%, PPV of 95%, NPV of 96%, and accuracy of 97%. Conclusion: PET/MRI exhibits high diagnostic accuracy in the staging of PCa, particularly in the assessment of local tumor extent, lymph node involvement, and distant metastases. The integration of PET/MRI into clinical practice may improve the accuracy of PCa staging, leading to more personalized treatment decisions and improved patient outcomes.